Effects of Li Salt Anions and O2 Gas on Li Dissolution/Deposition Behavior at Li Metal Negative Electrode for Non-Aqueous Li-Air Batteries. Issue 12 (1st January 2017) - Saito, Morihiro; Fujinami, Taichi; Yamada, Shinya; Ishikawa, Taro; Otsuka, Hiromi; Ito, Kimihiko; Kubo, Yoshimi
Abstract : To clarify the relationship between Li + transport rate in glyme-based electrolytes and Li deposition/dissolution behavior at Li metal negative electrode (NE) in Li-air batteries (LAB) systems, 1.0 M tetraglyme (G4) electrolytes were prepared containing a Li salt of LiSO3 CF3, LiN(SO2 CF3 )2, or LiN(SO2 F)2 . Two aspects of Li + transfer between the two phases, i.e., G4 electrolyte | Li metal NE, were evaluated, namely i) Li + supplying rate and ii) Li + charge transfer rate through solid electrolyte interphase (SEI) films. The former was investigated by self-diffusion coefficients D of Li +, anions, and G4 solvent together with ionic conductivity σ, viscosity, density, and apparent dissociation degree α app of the Li salts estimated by the Nernst–Einstein equation. The latter was evaluated with Li | Li symmetric and LAB (Li | O2 ) cells containing the electrolytes. The Li deposition/dissolution reaction basically depended on the Li + supplying rate in the Li | Li cell; however Li dendrites were formed. Conversely, the LAB cell performance was controlled by Li oxide layers formed on the NE, resulting in similar discharge/charge properties without Li dendrites. The effects of surface-oxidation was also confirmed with Li | Li cells containing O2 gas, where both SEI and charge transfer resistances were reduced.